Price Expectations in the United States: 1947-1973 - Jacobs, Rodney L.; Jones, Richard A. (American Economic Review, 1978)
It is common to assume that expectations about future inflation influence economic behavior. The behavior of an economic system over time is determined in part by the manner in which these expectations are formed. Theoretical and empirical investigations frequently utilize a hypothesis that agents forecast future inflation rates primarily on the basis of past inflation rates: static, adaptive, extrapolative, and regressive expectations adjustment schemes are examples of such forecasting rules.1 But such rules generally ignore the fact that individuals observe prices, not inflation rates. A change in observed prices can result from general price inflation, but it may also result from transitory shocks to the price level or observation error. Similarly, apparent changes in the general inflation rate may be purely transitory in nature or may signify the beginning of a trend. A model of inflation expectations should admit the possibility of these different sources of price change and embody the natural human tendency to extrapolate seeming trends. This paper examines the extent to which agents' reported price expectations are consistent with such naive forecasting. A multilevel adaptive expectations model is developed that takes observed prices as the information available to agents. On the basis of these prices, individuals revise their beliefs about not only the price level but also the underlying inflation rate and trend in the inflation rate. When fitted to the Livingston survey data the model appears to provide a unified explanation of price expectations in the United States from 1947 to 1975. This is contrasted with earlier investigations suggesting that expectations formation differed significantly in the periods before and after 1960.